Innovative Double-Finned absorber and Nanoparticle-Enhanced energy storage for enhanced Thermo-Economic performance of solar stills - Suraparaju, Subbarama Kousik; Samykano, Mahendran; Nandavarapu, Raveendra Reddy; Natarajan, Sendhil Kumar; Muthuvairavan, Guna; Yadav, Aman; Vasudevan, Gopi (Elsevier B.V., 2025)
This research investigates the potential of integrating nanoparticle-infused composite energy storage materials (CESM) with an innovative double-finned (DF) absorber in a single slope solar still (SSSS) to address the inefficiencies of conventional solar desalination systems. Traditional solar stills often face heat transfer and retention limitations, which hinder their overall performance. This study introduces a novel double-finned absorber, which optimizes thermal distribution by providing an expanded surface area for heat absorption and transfer within the system. Additionally, coal nanoparticles (CNPs) are incorporated into paraffin wax to develop composite energy storage materials, resulting in a 52.61 % improvement in thermal conductivity at the optimal nanoparticle concentration. Morphological analysis confirms the structural integrity of coal nanoparticles, ensuring reliable energy storage and release over repeated cycles. Experimental results demonstrate a remarkable 123 % increase in distillate yield compared to conventional solar stills. The proposed system achieves superior thermal management, with peak absorber temperatures reaching 68 °C, resulting in efficient and sustained water evaporation. Thermal efficiency improves to 51.38 %, nearly doubling the 29.88 % efficiency of conventional solar stills. Economic analysis reveals a significant reduction in water production costs to ₹1.25 per liter, with a payback period of just 4.5 months, highlighting the system's economic feasibility. This study underscores the synergistic effects of composite energy storage materials and advanced absorber designs, setting a new standard in solar desalination technology. The proposed system offers a sustainable and scalable solution to address global water scarcity challenges by significantly enhancing water yield, energy efficiency, and cost-effectiveness.